1996
DOI: 10.2109/jcersj.104.710
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Silica Glass Implanted with Phosphorus Ion at 50keV for Radiotherapy

Abstract: A chemically durable glass containing a large amount of phosphorus is useful for in situ irradiation of can cers. It can be activated to emitter with 14.3d half-life by neutron bombardment. Microspheres of the acti vated glass injected to the tumors can irradiate ray directly to the tumors without giving radiation to neighboring normal tissues. In order to examine possibility for obtaining such a glass by ion implantation, P+ ion was implanted into a pure silica glass in a plate form under 50keV to different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…9. [14][15][16][17][18] The SIMS spectrum indicates that the phosphorus ions are widely distributed in a layer that is centered at a depth of 200-250 nm. This spectrum suggests that the implanted phosphorus ions diffused inward and outward during the ion implantation, because the phosphorus concentration at the maxi- Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…9. [14][15][16][17][18] The SIMS spectrum indicates that the phosphorus ions are widely distributed in a layer that is centered at a depth of 200-250 nm. This spectrum suggests that the implanted phosphorus ions diffused inward and outward during the ion implantation, because the phosphorus concentration at the maxi- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 showed that an increasing amount of phosphorus ions can be implanted into the silica glass as the dose of the incident ion increases at least up to 1 × 10 18 cm −2 under an energy of 200 keV; at 20 keV, saturation occurred at 5 × 10 16 cm −2 , and, for 50 and 100 keV, saturation occurred at 5 × 10 17 cm −2 , as shown in the previous work. [14][15][16][17][18] These results indicate that the maximum amount of phosphorus ions that can be implanted into the glass increases as the implantation energy increases. This observation is explained by assuming that the maximum phosphorus concentration exists at a larger depth from the surface of the silica glass at 200 keV than at 20, 50, and 100 keV; i.e., the maximum concentrations of the phosphorus that has been implanted at 20, 50, 100, and 200 keV are theoretically estimated to be located at depths of 19.9, 48.6, 100.2, and 207.3 nm, respectively.…”
Section: (3) Chemical Durability Testmentioning
confidence: 99%
See 3 more Smart Citations